Microtensile Bond Strength and Failure Mode of Different Universal Adhesives on Human Dentin - Santander-Rengifo, Flor (2024)
Aim: The aim of this study was to compare the microtensile bond strength (µTBS) and failure mode of 4 different universal adhesive systems (UAs) on human dentin. Materials and methods: The study sectioned the occlusal thirds of 32 human third molars and divided them into 4 groups based on the adhesive system used. Group A: Palfique Universal Bond, Group B: Single Bond Universal, Group C: All-Bond Universal, and Group D: One Coat 7 Universal. The specimens underwent a 10,000-cycle thermocycling ageing process prior to testing (n = 32). Afterwards, 8 beams were obtained per group and subjected to µTBS testing using a digital universal testing machine at a speed of 1 mm/min. The microtensile bond strength values were analysed in Megapascals (MPa), and the failure mode was evaluated using a stereomicroscope. Welch's parametric ANOVA with robust variance and the Games-Howell post hoc test were used for µTBS comparisons, and Fisher's exact test was used to determine the association between adhesive type and failure mode. The significance level was set at P < .05. Results: Group D showed a significantly higher µTBS than groups A (P < .001) and B (P < .001), but no significant difference was observed with group C (P= .075). Furthermore, groups B and C showed significantly higher µTBS than group A (P< .001 and P < .001, respectively), but there was no significant difference between groups B and C (P = .132). Additionally, group A exhibited a significant association with an adhesive failure mode (P < .05), whereas groups B, C, and D were significantly associated with a mixed failure mode (P < .05). Conclusion: The One Coat 7 Universal adhesive system showed higher microtensile bond strength values and higher chemical interaction with dentin compared to Palfique Universal Bond and Single Bond Universal. However, no significant differences were observed compared to All-Bond Universal.